Assessing Dietary Practices of Children with Avoidant Restrictive Food Intake Disorder (ARFID) - A Cross-Sectional Study - Shafiq, Rabiya; Aziz, Ammara; Asif, Ghanva; Hussain, Muhammad Imran; Hayee, Aruj (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: The current study aimed to find children’s dietary patterns with Avoidant Restrictive Food Intake Disorder (ARFID) and its characteristics in children. METHODOLOGY: This mixed-method cross-sectional study conducted in April 2021 among children with Avoidant Restrictive Food Intake Disorder. Thirty participants of the age group (5-12 years) were selected from the Pediatrics and Children Ward of Ittefaq Hospital, Lahore, with a purposive sampling technique. Outpatient children aged between 5 and 12 years were included, whereas the children who had any congenital disabilities and were diagnosed with any other eating disorder were excluded. A focus group discussion was held for the formulation of the questionnaire. A diagnostic criteria questionnaire for ARFID was taken from the Canadian Pediatric Surveillance Program 2017, including anthropometric data and general characteristics/behavioral features. A self-structured food frequency questionnaire was used. Informed consent was taken from all participants. Qualitative interviews were reported as thematic analysis, and Quantitative data were analyzed using SPSS version 25 as statistical analysis for data visualization, simple statistics to generate summary charts, and customized graphs. RESULTS: Patients with ARFID were primarily female and relatively young, with a mean age of 8.35±0.46. Most of the participants were underweight (77%). The mean BMI (kg/m2) of children was 13.7±0.26. Most patients with ARFID also reported a lack of interest in eating, loss of appetite, aversion due to sensory characteristics and avoidance of certain foods. CONCLUSION: ARFID is prevalent in all populations, but the lack of awareness among healthcare professionals and the general population makes the diagnosis difficult.